Effects of transtympanic intermittent pressure therapy using a new tympanic membrane massage device for intractable Meniere's disease and delayed endolymphatic hydrops: a prospective study. (1st October 2021) - Shojaku, Hideo; Aoki, Mitsuhiro; Takakura, Hiromasa; Fujisaka, Michiro; Asai, Masatsugu; Tsubota, Masahito; Ito, Yatsuji; Watanabe, Yukio
Abstract: Background: The retrospective study showed that the effect of the middle ear pressure treatment by the tramstympanic membrane massage (TMM) device was similar to that of the Meniett device. Objectives: The new TMM device named EFET device was prospectively evaluated in patients with Meniere's disease (MD) and delayed endolymphatic hydrops (DEH) and we compared the effects to the Meniett device. Materials and methods: 23 ears of 19 patients were treated with an EFET device, and 17 ears of 15 patients were treated with the Meniett device. All patients suffering from intractable MD and DEH were treated for 4 months. The insertion of a transtympanic ventilation tube was necessary for the Meniett device, but not the EFET device. Results: In patients treated by the EFET and Meniett devices, the frequency of vertigo significantly improved after treatment. The distribution of vertigo outcomes at 4 months after treatment did not differ between patients treated with the both devices. Conclusions and significance: Middle ear pressure treatment by the EFET device is effective and provides minimally invasive options for intractable MD and DEH like the Meniett device.